INTERELASI AGAMA DAN BUDAYA - Pangulu Abdul Karim (NIZHAMIYAH, 2016)
Religion and culture has a very strong relationship, because both of them are  values and symbols. Religion is a symbol that represents the value of obedience to God. Culture also contain values and symbols so that people can live in the environment. However, it should be emphasized that there is a difference. Religion is already final, eternal, and does not recognize the change. Meanwhile the culture  can change. But both are able to shift due to both an historical fact.Kata Kunci: Interelasi, Agama, Budaya